IMPLEMENTATION OF EDUCATIONAL VALUES IN BOARDING DARUL FALAH AL WASHILAH MEDALEM SENORI TUBAN - Asrofi Asrofi; Djunaidi Ghony; Moh Muslim (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
The purpose of this study is to describe how the values of the pesantren are instilled in the Darul Falah Al-Washilah Islamic Boarding School. This study uses a qualitative method. The research results show that; 1) The values of Islamic boarding school education include sincere values, honest values, hard work values, responsibility values and tolerance values which are used as the basis for the behavior of all activities in Islamic boarding schools; 2) Integrating the values of Islamic boarding schools in subjects in schools and Islamic boarding schools; 3) Internalization of the values of Islamic boarding school education which are instilled in all pesantren residents and school members. The strategy used is through habituation and integrated training through extra-curricular activities and the creation of a culture of character in Islamic boarding schools. Moderate value planting is implemented in several methods, namely; first, diniyyah education, namely the recitation of the yellow books taught by several ustadz. Second, joint takror, namely repeating the subject matter that has been taught by the kiai or ustadz by asking one of the students to read word for word, then the other listens and corrects if there are errors in reading.